Pelvic Lymph Node Lymphangiomyomatosis Found During Surgery for Gynecological Fallopian Tube Cancer: A Case Report and Literature Review - Xiao, Shan; Chen, Yijia; Tang, Qianjue; Xu, Lianwei; Zhao, Li; Wang, Zhenzhen; Yu, Erkai (Frontiers in Medicine, 2022)
Background: Lymphangioleiomyomatosis (LAM) is a rare low-grade metastatic tumor with an unknown origin that spreads through lymphatic vessels. It is characterized by the proliferation of smooth muscle-like or epithelioid tumor cells in the lung and axial lymphatic system. Extrapulmonary LAM is a localized disease with a low incidence rate, and the location of the related lesions is atypical. It is difficult to diagnose. The LAM of pelvic lymph nodes is hidden. It is usually found through gynecological oncology surgery. Case presentation: We report a 57-year-old postmenopausal woman with a pelvic mass and vaginal bleeding as the main symptoms. The patient had no history of pulmonary LAM, tuberous sclerosis complex (TSC) or renal angiomyolipoma and had not used exogenous hormones. We performed a total hysterectomy, bilateral adnexectomy, greater omentum resection, pelvic lymphadenectomy and colonic nodule resection under laparoscopy. The postoperative pathology confirmed high-grade serous carcinoma of the left fallopian tube, and four lymph nodes were found in the pelvic lymph nodes, suggesting lymphangiomyomatosis. Immunohistochemical results also showed that these cells could express markers of smooth muscle cells and melanoma cells. The patient was treated with chemotherapy after the operation. Chest CT did not suggest lung LAM during the postoperative follow-up, and there was no tumor recurrence. Conclusion: The diagnosis of this disease is challenging. At the same time, due to insufficient clinical samples, it is still unknown whether there is a potential relationship between pelvic and peritoneal lymph node LAM found in the surgical staging of gynecological tumors and lung LAM and/or TSC. There is no evidence that pelvic and peritoneal lymph node LAM will increase the risk of pulmonary LAM. Therefore, additional clinical data are required to analyze and summarize the relationship between pelvic and peritoneal lymph node LAM, pulmonary LAM, and the source of LAM. We present a case of pelvic lymph node LAM and believe that the disease is highly similar to endometriosis.